2010
DOI: 10.1111/j.1600-9657.2010.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injuries during anaesthesia: part I: clinical evaluation

Abstract: The overall incidence of dental injury in our retrospective study was 1.38 per 1000 anaesthetics, which is slightly higher than those reported by some and lower with respect to others. Avulsion of a permanent tooth occurred in patients who were affected by severe mobility of native teeth while undergoing surgery. Even though the majority of anaesthesiologists were trained enough in the use of airway devices and aware of the potential damage while using excessive forces, some unexpected difficulties may have le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Dental injury is one of the frequent adverse events of intubation and the most common claim against intubators. 15 Previous research has shown that the complete arch of the incisors has maximum bite force ranging from 150 to 200 N. 16 Based on this information, the peak force on the maxillary incisors of more than 150–200 N might be a risk factor for dental injury during intubation attempts. Although some studies have reported that the use of VLs (ie, GlideScope, McGrath and V-MAC) were associated with less force applied on maxillary incisors, 8 17 our results showed the applied force was higher in the C-MAC group.…”
Section: Discussionmentioning
confidence: 99%
“…Dental injury is one of the frequent adverse events of intubation and the most common claim against intubators. 15 Previous research has shown that the complete arch of the incisors has maximum bite force ranging from 150 to 200 N. 16 Based on this information, the peak force on the maxillary incisors of more than 150–200 N might be a risk factor for dental injury during intubation attempts. Although some studies have reported that the use of VLs (ie, GlideScope, McGrath and V-MAC) were associated with less force applied on maxillary incisors, 8 17 our results showed the applied force was higher in the C-MAC group.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of force applied on the oral structures are surrogates of intubation-related complications, there is a linkage between the force applied on the oral structures and intubation-related complications [ 19 ]. For example, excess force on the maxillary incisors increases the risk of dental injury—a frequent adverse event of intubation, and is the most common claim against intubators [ 20 ]. According to the prior study, force on the maxillary incisors greater than 150 N could be a risk factor for dental injury [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, perioperative dental injuries occur with relatively high incidence (0.13%), especially for patients with dental problems. 15) Once dental injuries occur during anesthesia, the cost of treatment and compensation is problematic, and the patient-doctor relationship can deteriorate. 16) A tooth protector is useful for preventing dental injuries and can sometimes improve intraoral conditions after oral injuries.…”
Section: Discussionmentioning
confidence: 99%